AN EMPIRICAL STUDY ON HEALTH STATUS OF OLD AGED PEOPLE OF FISHERMEN’S COMMUNITY AND NON FISHERMEN’S COMMUNITY IN KALAPET, PUDUCHERRY - et. al., A.Thileeban (International Journal of Modern Agriculture, 2021)
From ancient period to present period, situation and the circumference of the old aged people in poor family has not been changed due to selfish characters of the both male and female people in India, thereby old aged people’s situation at inability time has been becoming so sad and pitiable as they are not able to live with family members supports and hold .Additionally health condition and status are varied from family to family ,income to income ,wealth to wealth and caste to caste ,all these problems are making social scientist and generous persons to feel bad and sad about their inexpressive situations in the Indian family system. India will not grow and develop only with the help of youngsters but also needed the help of old aged people’s at all the decision making process from family to government. If so, developments would occur itself from family to country toward achieving unimaginable success and victory in its all the progress and success. In every family children and daughter-in-law and family members have to pay humanitarian concern on caring and preserving the old people’s needs and necessities without any bias and discrimination. To do this work they have to think them as their parents who have nurtured them and shouldered all their weights until they become mature and younger